Kinesio Taping Efficacy and Demographic Correlates in Alleviating Plantar Fasciitis Pain - Selviani, Iit; Ilham, Ilham; Syafrianto, Donal; Okilanda, Ardo; Sari, Anggun Permata; Kurniawan, Randi; Crisari, Silvio; Arisman, Arisman (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
This research examines the efficacy of Kinesio taping therapies in reducing pain related to plantar fasciitis. A thorough technique was used, including systematic sampling, to choose 30 individuals. Applying inclusion and exclusion criteria ensured homogeneity. Demographic attributes such as age, height, weight, and BMI were painstakingly documented, resulting in a complete profile. The study methodology used a one-way analysis of variance (ANOVA) to compare pain levels, as evaluated by the Numerical Rating Scale (NRS), across various therapies. The data collection process included evaluations conducted before and after the intervention, which allowed for a comprehensive evaluation of the effectiveness of Kinesio taping. The paired sample t-test demonstrated a statistically significant reduction in pain levels (p = 0.001*), providing evidence to support the notion that Kinesio taping is a useful method for alleviating pain associated with plantar fasciitis. Despite the positive results, Johnson et al. (2020) expressed doubt, and the discussion acknowledges this by highlighting the impact of methodological variations and participant variables on the inconsistent results. The research promotes the use of established techniques, subgroup analyses, and thorough assessment methods to improve the dependability of results and resolve conflicting conclusions. Ultimately, this study provides significant knowledge on the possibility of Kinesio taping as a non-invasive treatment for plantar fasciitis. The favorable results emphasize its effectiveness, but a cautious interpretation is maintained, advocating for more study to get a more nuanced comprehension.